2012
DOI: 10.1590/s0100-879x2012007500049
|View full text |Cite
|
Sign up to set email alerts
|

Experimental model of heterotopic ossification in Wistar rats

Abstract: Heterotopic ossification (HO) is a metaplastic biological process in which there is newly formed bone in soft tissues adjacent to large joints, resulting in joint mobility deficit. In order to determine which treatment techniques are more appropriate for such condition, experimental models of induced heterotopic bone formation have been proposed using heterologous demineralized bone matrix implants and bone morphogenetic protein and other tissues. The objective of the present experimental study was to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…These are a lot of kinds of models of AHO that have been reported. (Zotz et al, 2012;Kan & Kessler, 2011) Achilles tenotomy model is widely used. McClure applied the model to mice and found that AHO developed by 10th weeks in 1983.…”
Section: Discussionmentioning
confidence: 99%
“…These are a lot of kinds of models of AHO that have been reported. (Zotz et al, 2012;Kan & Kessler, 2011) Achilles tenotomy model is widely used. McClure applied the model to mice and found that AHO developed by 10th weeks in 1983.…”
Section: Discussionmentioning
confidence: 99%
“…The first blood collection was from intracardiac puncture, 1 week before HO induction ( 16 ), giving the animals time to recover from the blood collection and any eventual blood loss. The experiment lasted 43 days: day 1 was the first blood collection, day 8 was HO induction, and day 43 was the day the animals were killed.…”
Section: Methodsmentioning
confidence: 99%
“…For the implant, a thin needle (0.3×16 mm) for insulin injection was inserted perpendicularly to the ventral side of the thigh. All animal groups received 0.35 mL of BM and were given oral doses of 20 mg·kg −1 ·24 h −1 dipyrone (500 mg/mL, Eurofarma, Brazil) during the first 3 days for pain relief after the BM collection procedure ( 16 ).…”
Section: Methodsmentioning
confidence: 99%
“…HO formation in rodents has been achieved but included cytokine modulation of the animal 35. The model produced by Tannous et al used local blast to the lower limb and therefore systemic causes of blast related HO were not taken into account 36.…”
Section: Required Researchmentioning
confidence: 99%